Effect of nickel in solid solution on the hydrogen embrittlement susceptibility of low alloy steels - Husby, H.; Johnsen, R.; Iannuzzi, Mariano; Barnoush, A.; Kappes, M.; Rebak, R. (2017)
© 2017 Chinese Society of Theoretical and Applied Mechanics. All Rights Reserved. In the oil and gas industry, the use of low alloy steels (LAS) in H2S containing environments is governed by ISO 15156-2. Nickel is limited to a maximum of 1 wt% due to sulfide stress cracking (SSC) resistance concerns. This work investigated the effect of solid solution nickel in the ferrite phase on hydrogen transport kinetics and hydrogen stress cracking (HSC) susceptibility. Ferritic/pearlitic research-grade LAS with nominal nickel contents of 0, 1, 2 and 3 wt% were examined. Electrochemical hydrogen permeability experiments were carried out to investigate hydrogen diffusion, solubility, and trapping in the steels. The relative HSC susceptibilities of the steels were determined by slow strain rate (SSR) testing with in situ hydrogen charging. Combining hydrogen permeability and SSR tests allowed for the quantification of the HSC resistance as a function of nickel content.